Analisa Asosiasi – Asosiasi Kesan Pasar Tangga Arung Tenggarong Yang Membentuk Kesan Konsumen - Hermanto, M. (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2008)
The main purpose of this research is to know Associations of impressionof shopping center in PasarTangga Arung Tenggarong for consumers. The analysis instrument used to know the Associations ofimpressionof shopping center in Pasar Tangga Arung Tenggarong for consumers is Cochran Q testwith SPSS program in analyzing data with a significant level of 5% until obtained the count statisticChi-square1.167and statistic table and 5.991 with 2 degrees,has obtained the significance of 0.558. Orthe statistical count is smaller than the rate of statistics table (1.167 <5, 991) and its significance valueis 0.558 or probability above0.05 (0.558> 0.05). Means showing the Associations of impressionofshopping center in Pasar Tangga Arung Tenggarong can form good impression for the consumers untilbecome interested to go shopping or visiting that market, so in conclusion,Ho (null hypothesis) isrejected and Ha (hypothesis altarnatif) received the 10 associations Pasar Tangga Arung Tenggarongindeed there alternative which formed an impression for the consumer.